Science at the Crossing of Conceptions - Tytmonas, Alfredas (Problemos, 1982)
An attempt is made in the article to throw light on some features of the development of science conceptions. The attention of the author is centred on such an aspect of science phenomenon interpretation as the removal of a gap between logical-gnoseological and sociological approaches to the theoretical interpretation of science in the pre-Marxist philosophy.